Mexico and the Republic of Serbia: 77 years of uninterrupted and productive diplomatic relations; new challenges and opportunities - Karlos Isauro Feliks Korona (Napredak, 2023)
In the archives of the Library of the University in Belgrade it is possible to find evidence that as early as 1844. the events in Mexico were written about in the old Serbian language, and that there was an interest in this country. Strong friendship and understanding between the two nations were formalized by the Protocol on the Establishment of Diplomatic relations on 24 May 1946, when the President of Mexico, Manuel Avila Camacho and the President of the Socialist Federal Republic of Yugoslavia, Marshal Josip Broz Tito, made this cooperation official. The closeness of these two peoples was most evident through their engagement in the Non-Alignment Movement and the promotion of the ideas of freedom and independence of each state, including their economic development. Such closeness, accompanied by mutual collaboration and assistance, has lasted for 77 years, to the satisfaction of both sides, with the perspectives of further strengthening and intensification.